2018
DOI: 10.1002/jpen.1484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Assessment of Resting Metabolic Rate in Critically Ill Patients

Abstract: Background Predicting resting metabolic rate (RMR) in mechanically ventilated, critically ill patients is an important part of the nutrition care in such patients. Methods RMR and associated clinical data from various studies of mechanically ventilated, critically ill patients were combined, and the impact of body size, age, reason for admission, and sedation level were analyzed along with prediction methods of RMR (the American Society for Parenteral and Enteral Nutrition [ASPEN] standards and the Penn State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
6
0
1
Order By: Relevance
“…Our results are consistent with prior findings that the ACCP recommendations are generally inadequate [11,12,30,34]. Frankenfield has suggested new generation of potential prediction equations to better account for BMI extremes [24]. However, these equations have yet to be validated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with prior findings that the ACCP recommendations are generally inadequate [11,12,30,34]. Frankenfield has suggested new generation of potential prediction equations to better account for BMI extremes [24]. However, these equations have yet to be validated.…”
Section: Discussionsupporting
confidence: 91%
“…This study on a large number of critically ill adult medical patients showed a decrease in measured EE with increasing age. Frankenfield has described in his recent detailed retrospective analysis of data from 826 critically ill patients that aging is associated with a nonlinear decrease in resting EE [24]. We have also observed that increasing BMI and female gender were independent determinants of an increase in EE adjusted for IBW after adjustment for several clinical factors.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, weight and age were the ‘static’ variables selected for use in the prediction models of both the acute and late phases. Older patients may have lower REEs partly because of age-associated changes in body composition and the relative size of fat-free mass (FFM) components [ 27 , 34 , 35 ]. Many studies have shown that body weight and FFM (the metabolizing mass of the body) correlate with REE [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Por esta razón, la predicción es el método más utilizado en la práctica clínica para determinar el gasto energético (GE). Existen numerosos factores que tienen una influencia en el GE de estos pacientes: tamaño y composición corporal, edad, sedación, tipo de alimentación, patología de base y la temperatura corporal, entre otros 40 . En la tabla 1 se muestran los requerimientos energéticos y proteicos de pacientes con COVID-19 no críticos de acuerdo con las distintas guías internacionales.…”
Section: Importancia De La Terapia Nutricional En El Paciente Hospitaunclassified